Ω-3 Fatty Acids Prevent Hepatic Steatosis, Independent of PPAR-α Activity, in a Murine Model of Parenteral Nutrition–Associated Liver Disease. (July 2014) - Prince, Esther; Lazare, Farrah B.; Treem, William R.; Xu, Jiliu; Iqbal, Jahangir; Pan, Xiaoyue; Josekutty, Joby; Walsh, Meghan; Anderson, Virginia; Hussain, M. Mahmood; Schwarz, Steven M.
Objectives : ω-3 Fatty acids (FAs), natural ligands for the peroxisome proliferator-activated receptor–α (PPAR-α), attenuate parenteral nutrition–associated liver disease (PNALD). However, the mechanisms underlying the protective role of ω-3 FAs are still unknown. The aim of this study was to determine the effects of ω-3 FAs on hepatic triglyceride (TG) accumulation in a murine model of PNALD and to investigate the role of PPAR-α and microsomal triglyceride transfer protein (MTP) in this experimental setting. Methods : 129S1/SvImJ wild-type or 129S4/SvJaePparatm/Gonz/J PPAR-α knockout mice were fed chow and water (controls); oral, fat-free PN solution only (PN-O); PN-O plus intraperitoneal (IP) ω-6 FA-predominant supplements (PN–ω-6); or PN-O plus IP ω-3 FA (PN–ω-3). Control and PN-O groups received sham IP injections of 0.9% NaCl. Hepatic histology, TG and cholesterol, MTP activity, and PPAR-α messenger RNA were assessed after 19 days. Results : In all experimental groups, PN feeding increased hepatic TG and MTP activity compared with controls. Both PN-O and PN–ω-6 groups accumulated significantly greater amounts of TG when compared with PN–ω-3 mice. Studies in PPAR-α null animals showed that PN feeding increases hepatic TG as in wild-type mice. PPAR-α null mice in the PN-O and PN–ω-6 groups demonstrated variable degrees of hepatic steatosis, whereas no evidence of hepatic fat accumulation was found after 19 days of oral PN plus IP ω-3 FAs. Conclusions : PN induces TG accumulation (steatosis) in wild-type and PPAR-α null mice. In PN-fed wild-type and PPAR-α null mice given IP ω-3 FAs, reduced hepatic TG accumulation and absent steatosis are found. Prevention of steatosis by ω-3 FAs results from PPAR-α–independent pathways.